Development and validation of novel automatable assay for cholesterol efflux capacity. Issue 2 (7th February 2023) - Mutsuda, Yume; Miyakoshi, Tsunehiro; Horiuchi, Yuna; Kameda, Takahiro; Tozuka, Minoru; Ohkawa, Ryunosuke
Abstract: During the past decade, evaluation of high-density lipoprotein (HDL) functionality has been well studied for predicting cardiovascular disease (CVD) risk. Cholesterol efflux capacity (CEC) is the strongest candidate as the biomarker out of various HDL antiatherosclerotic functions. However, CEC has not yet been introduced clinically because of several technical issues, including the use of radioactive materials and differentiated cells in the assay. Previously, our laboratory developed a radioisotope- and cell-free CEC assay called the immobilized liposome-bound gel beads (ILGs) method to replace the conventional method. However, the separation process of the supernatant was not suitable for installation in an automatic analyzer. The present study aims to develop a new method that is easier to operate. We assumed that the use of magnetic beads instead of gel beads would enable the skip of the centrifugal process. First, similar to the ILG method, porous magnetic beads were treated with liposomes containing fluorescently labeled cholesterol. Fluorescence was observed inside the magnetic beads, and almost the same amount of liposomes as in the ILG method was immobilized successfully. These immobilized liposome-bound magnetic beads (ILMs) were available for CEC assay when HDL and apolipoprotein B-100-depleted serum (BDS) were used as cholesterol acceptors. The ILM method showed sufficient basic performance and a good correlation with the ILG method. Furthermore, when the CEC of 15 serum samples from healthy subjects was measured, a good correlation between HDL-cholesterol level and the ILG method was confirmed. Thus, it was confirmed that the ILM method was successfully developed and could be automated.